AB1142 Severe life-threatening septic sacroiliitis in two otherwise healthy adolescents. (23rd January 2014) - Iglesias, E.; Camacho, M.; Hurtado, A.; Gomez, C.; Falcon, L.; Obando, I.; Neth, O.
Abstract : Background: Staphylococcus aureus is a frequent cause of infections in children, ranging from skin and soft tissue to invasive life-threatening infections (1). Sacroiliac (SI) joint is a rare site of septic arthritis although more frequent in children than adults patients (2). Non-specific symptoms make diagnosis challenging whilst radiological imaging and cultures confirm clinical suspicion. Objectives: We report two case reports of otherwise healthy girls who presented to us with aggressive septic sacroiliitis and pyomyositis. Results: Case report 1: 13-year-old obese girl presents with a 5-day history of left gluteus pain. Examination showed furuncles of lower extremities, inability to walk and positive FABERE test. X-ray and US of hips were normal. Symptomatic treatment was started and 2 days later she developed worsening symptoms with high fever. Blood test: WBC 6290, neutrophils 64.8%; CRP 287 mg/L. She commenced empiric therapy with cloxacillin and improved clinically. MRI showed left sacroiliitis with extensive inflammatory disease affecting pelvic area, psoas and paravertebral muscles with abscess formation (image 1). Blood cultures remained negative; however due the aggressiveness of the illness clindamycin was added to treatment. Echocardiography ruled out endocarditis and a bone scan was negative. After 4 weeks of empiric iv antibiotic therapy and continuous clinical, laboratory and radiological improvement antibiotics were changed to oral for a total of 6 weeks. Long-term follow-up showed SI osteoarthritis. Case report 2: 11-year-old obese girl with a 2-day history of right lumbar and gluteus pain. Examination revealed furuncles of lower extremities, inability to walk and positive FABERE test. Normal hip x-ray and US. 2 hours after initiation of anti-inflammatory therapy she developed high fever with worsening clinical symptoms including arthritis of elbow and ankle, appearance of vasculitic lesions on palm and septic emboli lesions of lower extremities. Blood test: WBC 19100, neutrophils 89%; CRP 303 mg/L. Empiric therapy with vancomycin plus clindamycin for suspected methicillin resistant S. aureus was initiated. MRI of hips and SI showed right SI septic arthritis with iliac and sacral osteomyelitis and pyomyositis and multiple abscesses formation (image 2) requiring US guided drainage. Echocardiography ruled out endocarditis. Blood cultures continued to be positive for methicillin susceptible S. aureus with induced resistance to clindamycin and therapy was changed to high dose cloxacillin plus rifampicin with slow but continuous clinical improvement. Conclusions: Cutaneous lesions and rarely but importantly septic sacroiliitis can be presenting features of life-threatening infections due to S. aureus . Early diagnosis and initiation of appropriate management can be lifesaving. References: Sattler CV, Correa AG. Coagulase-positive staphylococcal infections (Staphylococcus aureus). In: Feigin RD, Cherry JD, Demmler GJ, Kaplan SL, eds. Textbook of Pediatric Infectious Diseases. 5th ed. Philadelphia, PA:Saunders; 2004:1099-1129 Wu MS, Chang SS, Lee SH and Lee CC. Pyogenic sacroiliitis-a comparison between paediatric and adult patients. Rheumatology 2007;46:1684-1687 Disclosure of Interest: None Declared